The Role of Place Identity in The Resiliency of Kalipasir Mosque as a Cultural Heritage Building - Ischak, Mohammad; Winandari, Maria Immaculata Ririk; Wijayanto, Punto; Aziiz, Akhlish Diinal; Karista, Ardilla Jefri (Universitas Muhammadiyah Surakarta, 2025)
The existence of Kalipasir Mosque as a Cultural Heritage building is one of the character-defining elements of the Pasar Lama Cultural Heritage area in Tangerang, Banten. Currently, Kalipasir Mosque is situated in the middle of a densely populated settlement and has become one of the tourist destinations in the Pasar Lama area. A prominent characteristic of the settlement's growth around the mosque is the large number of migrants who have moved and settled there, primarily due to the convenient and easy access to Tangerang city center. This phenomenon leads to a research question: Can the Kalipasir Mosque building sustain itself as a cultural heritage site amidst the changing characteristics of its surrounding settlements? A descriptive-analytical research method is employed to examine the place-making that occurs in the spaces around the mosque, shaped by the activities carried out by residents living in the adjacent settlement. Data exploration was conducted through interviews and data collection via questionnaires distributed to residents and worshippers around the mosque. The results of this research show that place identity plays a crucial role in the resilience of Kalipasir Mosque as a Cultural Heritage building. This place identity is shaped by several factors: the designation of Kalipasir Mosque as a Cultural Heritage building, the occurrence of religious and educational tourism, and the resulting pride felt by residents in the surrounding settlements.